Microstructural, mechanical and tribological characterization of aluminum-alloyed ductile cast irons based on aluminum content - Sandikoglu, Acelya; Gecu, Ridvan (ELSEVIER SCIENCE SA, 2021)
The ductile irons of EN-GJS-400-15 grade were alloyed with various amounts of Al from 0 to 4 wt% by induction furnace melting. After fabrication, the Al-alloyed cast irons were characterized by XRD, SEM, EDS, optical microscope equipped with image analysis software, mechanical tests including hardness, tensile and Charpy V-notch tests, and dry sliding ball-on-disc type wear tests against Al2O3 ball. It was determined that the amount of ferrite phase and nodule counts increased and nodularity decreased with increasing Al content until it reached 4 wt%, which caused a huge pearlite formation with an improved nodularity and reduced graphite size. An increase in the amount of Al provided the increase in the ultimate tensile strength, yield strength, and hardness while it caused the decrease in elongation and impact strength as expected. Worn surface examinations demonstrated that the samples were suffered from abrasive and adhesive wear during sliding tests. The best wear resistance was achieved by the 4 wt% Al-alloyed nodular cast iron, given microstructural and mechanical properties. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Ductile cast iron; Alloying; Aluminum; Graphite; Nodularity; Wear; WEAR BEHAVIOR; RESISTANCE; COMPOSITE; FRICTION; LAMELLAR; SIZE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering